2021
DOI: 10.1253/circj.cj-20-1148
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Fetal Left Ventricular Noncompaction in Japan

Abstract: We conducted nationwide retrospective surveys of fetuses with cardiomyopathies (CMs) in Japan January 2010 to December 2016, by which we aimed to elucidate the clinical features, diagnosis, and prognosis of fetal LVNC. Methods SubjectsWe conducted a multicenter, retrospective, observational study by inviting 131 hospitals with a fetal or pediatric cardiology department in Japan to participate in a survey of fetal patients with CMs from. After agreeing to participate, we sent a detailed questionnaire and DVD to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Ozawa et al estimate that the incidence of LVNC is 1.49 per 100,000 babies. 9 These data are compatible with data from a previous report 11 that showed that LVNC occurred in 0.81 per 100,000 infants/year. As reported, the prognosis in infants with LVNC is poor because of heart failure and/ or concomitant congenital heart disease.…”
Section: Irb Informationsupporting
confidence: 92%
See 1 more Smart Citation
“…Ozawa et al estimate that the incidence of LVNC is 1.49 per 100,000 babies. 9 These data are compatible with data from a previous report 11 that showed that LVNC occurred in 0.81 per 100,000 infants/year. As reported, the prognosis in infants with LVNC is poor because of heart failure and/ or concomitant congenital heart disease.…”
Section: Irb Informationsupporting
confidence: 92%
“…Ozawa et al propose that an N/C ratio ≥1.6 at the LV apex on fetal echocardiography is a possible predictor of LVNC after birth. 9 However, their study was retrospective, and…”
Section: Irb Informationmentioning
confidence: 98%
“…Indeed, we reported that sarcomere variants are most commonly identified in fetus-onset patients, and fetus-onset patients with LVNC are more likely to develop HF (90). Moreover, we found a time-dependent increase in the ratio of noncompacted to compressible layers (N/C) of the LV wall in patients with fetal-onset LVNC, with the N/C ratio being greater than 2 before and after birth (91). This change is in contrast to patients with DCM and HCM, suggesting that the formation of the trabeculated layer proceeds late in gestation.…”
Section: Theoretical Gap Among Human and Non-human Models Or Congenit...mentioning
confidence: 75%
“…The prognosis of newborns with mitochondrial disease or metabolic complications is worse, with a higher rate of heart transplantation compared to DCM in children (17). Additionally, fetal-onset cases have a high rate of HF and mortality (5,90,91). In contrast, young and adult-onset cases that are asymptomatic and detected by medical examination or incidentally often have isolated LVNC, are asymptomatic for a long time, and have a good prognosis (17).…”
Section: Natural Historymentioning
confidence: 99%
“…15 Additionally, the myocardial manifestations of this fetus were not consistent with hypertrophic cardiomyopathy (HCM, Z-scores of septal and posterior ventricular wall thicknesses greater than 2) or dilated cardiomyopathy (DCM, ventricular dilatation with a cardiothoracic ratio greater than 0.35 complicated with left ventricular dysfunction and left ventricular shortening rate less than 28%). 16 Therefore, the diagnosis of FVNC in this fetus was suggested. Besides, the fetus also showed findings of tricuspid regurgitation and pericardial effusion on ultrasound in late pregnancy with a CVPS of 7/10, indicating a poor prognosis.…”
Section: Discussionmentioning
confidence: 97%